CRISPR-Cas9-Mediated Silencing of CD44 in Human Highly Metastatic Osteosarcoma Cells - Tang Liu; Zuyun Yan; Yong Liu; Edwin Choy; Francis J. Hornicek; Henry Mankin; Zhenfeng Duan (Cellular Physiology and Biochemistry, 2018)
Background/Aims: Metastasis is the major cause of death in patients with osteosarcoma. There is an urgent need to identify molecular markers that promote metastasis. Cluster of differentiation 44 is a receptor for hyaluronic acid (HA) and HA-binding has been proven to participate in various biological tumor activities, including tumor progression and metastasis. Methods: We performed a meta-analysis to investigate the relationship between CD44 expression, survival, and metastasis in patients with osteosarcoma. We then utilized the CRISPR-Cas9 system to specifically silence CD44 in highly metastatic human osteosarcoma cells (MNNG/HOS and 143B) and further determined the functional effects of CD44 knockout in these cells. Results: The meta-analysis demonstrated that a high level of CD44 may predict poor survival and higher potential of metastasis in patients with osteosarcoma. The expression of CD44 in highly metastatic human osteosarcoma cell lines was efficiently blocked by CRISPR-Cas9. When CD44 was silenced, the proliferation and spheroid formation of these osteosarcoma cells was inhibited under 3-D culture conditions. Furthermore, the migratory and invasive functions were also impaired in these highly metastatic osteosarcoma cells. Conclusion: These results suggest that developing new strategies to target CD44 in osteosarcoma may prevent metastasis and improve the clinical outcome of osteosarcoma patients.